2015
DOI: 10.1523/jneurosci.1641-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inhibition of miR-155 Promotes Recovery after Experimental Mouse Stroke

Abstract: A multifunctional microRNA, miR-155, has been recently recognized as an important modulator of numerous biological processes. In our previous in vitro studies, miR-155 was identified as a potential regulator of the endothelial morphogenesis. The present study demonstrates that in vivo inhibition of miR-155 supports cerebral vasculature after experimental stroke. Intravenous injections of a specific miR-155 inhibitor were initiated at 48 h after mouse distal middle cerebral artery occlusion (dMCAO). Microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
132
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 96 publications
11
132
1
Order By: Relevance
“…These data suggest that stabilization of ZO‐1 in the OGD/I group of cells was not mediated via miR‐155 direct targets Rheb and RhoA. Taken together, analyses of the cell junction proteins revealed that miR‐155 inhibition in the OGD‐subjected HBMECs led to ZO‐1 stabilization, which is in agreement with previous studies on neuroinflammation and experimental ischemia 18, 29…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These data suggest that stabilization of ZO‐1 in the OGD/I group of cells was not mediated via miR‐155 direct targets Rheb and RhoA. Taken together, analyses of the cell junction proteins revealed that miR‐155 inhibition in the OGD‐subjected HBMECs led to ZO‐1 stabilization, which is in agreement with previous studies on neuroinflammation and experimental ischemia 18, 29…”
Section: Resultssupporting
confidence: 91%
“…ZO‐1 upregulation was also reported after the in vivo inhibition of miR‐155. In these studies, we proposed that ZO‐1 stabilization was mediated by miR‐155 direct target protein Ras homolog enriched in brain (Rheb) 18, 27. However, in the present study, Rheb levels were not affected by miR‐155 inhibition or overexpression (which probably means that in vivo experiments detected the combined Rheb levels in the endothelial cells, as well as microglia and astrocytes).…”
Section: Resultscontrasting
confidence: 76%
See 3 more Smart Citations